Smart and sassy : the strengths of inner city Black girls - Stevens, Joyce West, 1936- (New York : Oxford University Press, 2002)
Empirically based, the daily experiences of adolescent black females is explicated within an explanatory model of social context and developmental theory. The author argues that adolescence must be seen from strength and health perspectives.
Foreword -- Acknowledgments -- Prologue: A Book about the Strengths of Inner-City Black Girls -- PART 1 THEORY OVERVIEW -- 1 Risk and Resiliency in Social Contexts -- 2 Adolescent Developmental Theories -- 3 Person-Process-Context: An Ecological Transactional Model -- PART 2 DEVELOPMENTAL DOMAINS -- 4 Racial, Ethnic, and Gender Role Commitment -- 5 Care Protective Sensibility and Role Model Formulation -- 6 Decision Making, Dating, and Mate Selection Expectations -- 7 Opportunity Mobility and Adulthood Preparation -- PART 3 CLINICAL IMPLICATIONS -- 8 A Social Work Practice Model: Core Principles of Intervention -- Epilogue -- Glossary -- References -- Index.
Includes bibliographical references (pages 191-204) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: African American teenage girls -- Attitudes; African American teenage girls -- Psychology; African American teenage girls -- Social conditions; Adolescence -- United States; Adolescentes noires américaines -- Attitudes; Adolescentes noires américaines -- Psychologie; Adolescentes noires américaines -- Conditions sociales; Adolescence -- États-Unis.; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers; Adolescence; African American teenage girls -- Attitudes; African American teenage girls -- Psychology; African American teenage girls -- Social conditions; United States